Estudio de Factibilidad para la Creación de una Empresa Productora y Comercializadora de Café Arábigo en Sobres Filtrante, en la Ciudad de Loja - Yunga Salinas, Alvaro Lenin (2017)
Many economic sectors in most of our country agree that support for microenterprise is the way to reactivate production in Ecuador, however there are several limitations for this sector to achieve continuous growth, which is why Seeks to boost entrepreneurship or innovate business ideas by generating jobs and helping the country's economy. For this reason it has been considered convenient to carry out a "FEASIBILITY STUDY FOR THE CREATION OF A PRODUCTION AND MARKETING COMPANY OF ARABBIAN CAFÉ IN FILTERING ENVELOPE, IN THE CITY OF SHOP" considering it an innovative product, by giving Lojano coffee a value added by the Practicality of the product and the speed of its use; Minimizing time and money to the final consumer. For the execution of the present study, different materials, methods and research techniques were considered that allowed to gather information necessary to later analyze and to implement it in the later studies. These methods were: Deductive, Inductive and Analytical, while the techniques used was the survey, interview and direct observation. For the segmentation of the market was taken the population of the city of Loja, in the year 2010; According to the National Institute of Statistics and Censuses (INEC) were 180,671 inhabitants and a projection was made according to the growth rate of 2.65% for the year 2016 resulting in 211,306 inhabitants to later diversify it by family resulting in A sample of 52,827 families with whom they proceeded to work 6 For the implementation of the present feasibility study, an analysis was carried out in order to know the reception and profitability that this product will have in the city of Loja. The following studies were considered: The market study analyzed the supply and demand of this product in the market, obtaining an effective demand of 598,445,809 grams of Arabica coffee a year; And an unsatisfied demand of 542,909,809 grams in the first year; Likewise the marketing plan will be made in the form of Producer - Distributor - Final consumer. The technical study analyzes machinery, equipment, labor, which will be used for the manufacture of coffee filtering envelopes, as well as know the processing processes, as well as the installed capacity which is 65'700.000 grams per year, Which gives us a result for envelopes of 16'425,000 a year. While the capacity used is 15,600,000 grams per year and 3,900,000 envelopes per year. Legal Administrative Study, it was established that the company will be constituted as a corporation, with a number of five shareholders, as well as the organizational charts and manuals of functions that will have to fully fulfill the members of the company. In the Financial Study, the initial investment of the project is determined, being this one $ 68,157.31; A financing from a local financial institution such as "BanEcuador" will be incurred, this entity will finance 29% of the total value of the investment. Likewise, indicators such as the Net Present Value (NPV), which yields a positive result of $ 223,028.74, the Cost Benefit Ratio (RCB) is $ 7 0.31 ctv. Of profit for each dollar invested, in the Internal Rate of Return was obtained a percentage of 74% that is greater to the opportunity cost of capital, whereas the Period of Capital Recovery indicated that the investment realized will be recovered in the lapse of 1 Year 7 months 25 days, according to the Sensitivity Analysis it was obtained that with an increase in costs of 17.00% a sensitivity value of 0.99 is obtained and decreasing the income to 13.00% a value was obtained Of sensitivity of 0,99. Once the various studies were carried out, the respective conclusions and recommendations.